2012
DOI: 10.21059/buletinpeternak.v34i3.85
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penambahan Ampas Virgin Coconut Oil dalam Ransum terhadap Performan dan Produksi Karkas Ayam Broiler (The Effect of Virgin Coconut Oil Waste in the Diet of Broiler Chicken on the Performance and Carcass Production)

Abstract: INTISARIPenelitian ini bertujuan untuk mengetahui pengaruh pemberian ampas Virgin Coconut Oil (VCO) terhadap performan dan produksi karkas ayam broiler. Seratus dua puluh lima ekor ayam broiler ditempatkan pada 5 kelompok perlakuan pakan yang berbeda, yaitu R-0 (ransum basal), R-0,5 (0,5% ampas VCO), R-1,0 (1,0% ampas VCO), R-1,5 (1,5% ampas VCO), R-2,0 (2,0% ampas VCO). Setiap kelompok perlakuan pakan terdiri dari 5 replikasi masingmasing dengan 5 ekor. Ayam broiler dipelihara selama 5 minggu, setiap akhir mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
1
1
0
3
Order By: Relevance
“…Rapid microbial growth is also more likely to occur as pH levels decrease. These findings were reported by Oktaviana, D. (2009), who explained that as meat pH levels increase, Microbial growth will be rapid and lactic acid production will rise. Based on the analysis of lactic acid and pH levels in broiler meat samples from different RPAs, it can be concluded that RPA 1 has the highest levels of lactic acid and lower pH values due to the resting time given to the chickens before slaughter.…”
Section: Research Results and Discussionsupporting
confidence: 53%
“…Rapid microbial growth is also more likely to occur as pH levels decrease. These findings were reported by Oktaviana, D. (2009), who explained that as meat pH levels increase, Microbial growth will be rapid and lactic acid production will rise. Based on the analysis of lactic acid and pH levels in broiler meat samples from different RPAs, it can be concluded that RPA 1 has the highest levels of lactic acid and lower pH values due to the resting time given to the chickens before slaughter.…”
Section: Research Results and Discussionsupporting
confidence: 53%
“…The higher the protein content in the dough, the better its ability to bind water. The ability to hold water is directly proportional to the high protein content of meat which plays a role in chemically binding water [23]. So if the concentration of flour used in the manufacture of kambu crab increases, it will lower the proportion of protein that affects the process of water binding energy of the material.…”
Section: Bite Testmentioning
confidence: 99%
“…Protein ini berfungsi bagi daya ikat air karena protein tersebut merupakan komponen utama yang berfungsi dalam menahan air daging. Hal ini di perkuat dengan pendapat Oktaviana et al (2010) bahwa semakin meningkat kadar protein daging ayam broiler, menyebabkan daya ikat air semakin meningkat air secara kimiawi dan semakin menurun kadar lemak daging.…”
Section: Jurnal Ilmiah Agrisainsunclassified